Determinants of Capital Structure: Evidence from Indonesian Property and Real Estate Firms - Lailatus Sa’adah; Mohamad Soedarman (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study investigates the determinants of capital structure in property and real estate firms listed on the Indonesia Stock Exchange over the 2022–2024 period. Specifically, it examines the effects of profitability, liquidity, asset structure, and taxation on firms' capital structure decisions. A quantitative approach was employed using purposive sampling, resulting in a final sample of 19 firms with 52 observations after outlier removal. Secondary data were obtained from annual financial statements and analyzed using multiple linear regression. The results reveal that profitability, liquidity, and asset structure do not have a significant effect on capital structure. In contrast, taxation has a positive and significant effect, indicating that firms tend to increase leverage to benefit from tax shield advantages. These findings suggest that external factors, particularly taxation, play a more prominent role than internal financial characteristics in determining capital structure in the Indonesian property and real estate sector.